2022
DOI: 10.1021/acsami.2c08561
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Self-Cleaning Evaporators for Highly Efficient Solar Desalination Using a Highly Elastic Sponge-like Hydrogel

Abstract: Interfacial evaporation using light-absorbing hydrogels offers efficient solar evaporation performance under natural sunlight, ensuring an affordable clean water supply. However, achieving light-absorbing hydrogels with durable and efficient utilization is still a challenge due to inevitable salt accumulation, a difficult-to-control surface morphology, and poor mechanical properties on the surfaces of hydrogel-based evaporators. In this work, a photothermal sponge-like hydrogel with a 3D interconnected porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Thus, there were main factors that reduced the thermal conductivity of the SBF aerogels. 13,30 The surface morphologies of the SBFAP aerogel were observed as shown in Figure 3d−f. It was observed that the SBFAP material also possessed 3D interconnected porous structures with the similar pore size and pore wall thickness.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, there were main factors that reduced the thermal conductivity of the SBF aerogels. 13,30 The surface morphologies of the SBFAP aerogel were observed as shown in Figure 3d−f. It was observed that the SBFAP material also possessed 3D interconnected porous structures with the similar pore size and pore wall thickness.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, Figure S12a presents the water evaporation rate with error bars, indicating that the SSG system’s evaporation rate was also dependent on the indoor conditions during the experiments, such as room humidity and temperature . The increase in the water evaporation performance at a higher thickness of the SBFAP could be attributed to (1) the increased side surface area, leading to the enhanced water evaporation area (steam escape area) and (2) the heat harness from the surrounding environment and bulk water by the side surface. ,, Since the SBFAP material had a low thermal conductivity in the wet conditions (0.137 W m –1 k –1 ), its thermal insulation property could be improved with increasing thickness. As a result, the temperature of SBFAP’s side surface under 1 sun illumination was lower than that of the bulk water and the ambient air.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photothermal hydrogel-based solar evaporators have been emerged as a potential material for proficient clean water production. Several photothermal materials based on carbon (e.g., carbon nanotubes or graphene), ,, MXenes, , biomass materials, polymers, , metals, and metal oxides have been incorporated inside the hydrophilic gel to increase the local heat and improve the evaporation performance. However, exploring a low-cost photothermal evaporator with effective thermal management is the need of the hour.…”
Section: Introductionmentioning
confidence: 99%